An Analysis of the Mechanical Characteristics and Constitutive Relation of Cemented Mercury Slag. (25th October 2017) - Li, Xinwei; Zhang, Sui; Yan, E-chuan; Shu, Duoyou; Cao, Yangbing; Li, Hui; Wang, Siyang; He, You
Abstract : This study focuses on mercury slag in the Tongren area of Guizhou Province, China. Computed tomography (CT) is used with uniaxial and triaxial compression tests to examine the mechanical changes in cemented mercury slag and its formation. The CT results for the uniaxial compression test reveal the overall failure process of the mercury slag structure. Based on the coarse-grained soil triaxial test, a modified Duncan-Chang model is compared with the actual monitoring results and is found to be suitable for the analysis of the slag constitutive model.